MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI GAYA STRADDLE MELALUI PERMAINAN HALANG RINTANG KELAS V SD MUHAMMADIYAH 1 PEKAJANGAN (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of the research to enhancing the learning outcomes to determine the high-style straddle jumpthrough hurdles haling permaianan approach. This study is the use of action research. Meetings in this studydesigned two cycles, The object used is class V SD Muhammadiyah 1 Pekajangan Kedungwuni PekalonganDistrict in the second semester of academic year 2012/2013. The samples used were 22 students consisting of 8boys and 14 student daughter. Instruments used in data collection was obtained from the results of performancetests that students displayed during the implementation of the test. The conclusion of this study is the use of themethod of approach steeplechase game to improve learning outcomes straddle style high jump in class V SDMuhammadiyah 1 Pekajangan Kedungwuni Pekalongan District school year 2012/2013.